Impact of Banking Competition on the Use of Soft Information - Bertrand, Jérémie; Statnik, Jean-Christophe (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2019)
Over the past 20 years, scholars have discussed the impact of banking competition on the choice between transactional and relationship lending technologies extensively, but no resolution has emerged. To address these questions, this article uses a new measure of relationship lending that accounts for the actual level of soft information that banks use in their loan pricing. With this new measure, the analysis reveals that banks prefer to implement relationship lending technology when competition is weak. In addition and in accordance with extant theoretical conclusions, the shape of the relationship between competition and relationship banking is nonlinear and concave.